Three Supernumerary Marker Chromosomes in a Patient with Developmental Delay, Mental Retardation, and Dysmorphic Features. (15th June 2011) - Hu, Jie; Madan-Khetarpal, Suneeta; Serrano Russi, Alvaro H.; Kochmar, Sally; DeWard, Stephanie J.; Sathanoori, Malini; Surti, Urvashi
Abstract : We characterized three supernumerary marker chromosomes (SMCs) simultaneously present in a 2-year- and 10-month-old male patient with mental retardation and dysmorphic features. Peripheral blood chromosome analysis revealed two to three SMCs in 25/26 cells analyzed. The remaining one cell had one SMC. Microarray comparative genomic hybridization (aCGH) showed mosaicism for gains of 5q35.3, 15q11.2q13.3, and 18p11.21q11.1 regions. All three gains contain multiple OMIM genes. FISH studies indicated that one of the SMCs is a dicentric ring 15 with two copies of the 15q11.2q13.3 region including SNRPN/UBE3A and two copies of the 5q35.3 region. One of the der(18)s contains the 18 centromere and 18p11.2 regions, while the other der(18) has a signal for the 18 centromere only. The phenotype of the patient is compared with that of patients with tetrasomy 15q11.2q13.3, trisomy 5q35.3, and trisomy 18p11.2. Our study demonstrates that aCGH and FISH analyses are powerful tools, which complement the conventional cytogenetic analysis for the identification of SMCs.